Erratum to: Rapid and efficient identification of the mouse leptin receptor mutation (C57BLKS/J-Leprdb) by tetra-primer amplification refractory mutation system-polymerase chain reaction (ARMS-PCR) analysis - Harry Jung; Hajin Nam; Jun-Gyo Suh (Laboratory Animal Research, 2016)
We designed 4 primers for amplification of allelespecific PCR products from leptin receptor mutant and normal alleles using primer design web service for tetraprimer ARMS-PCR (Figure 1) i.e., Lepr-forward outer primer (Lepr-FO); 5′-AGGATACAATACAAGAACAA AAAGCCTG-3′, Lepr-forward inner primer (Lepr-FI); 5′-TATTAGAAGATGTTTACATTTTGATGGAGGG-3′, Lepr-reverse inner primer (Lepr-RI); 5′-GTCATTCAAA CCATAGTTTAGGTTTGTTTA-3′, Lepr-reverse outer primer (Lepr-RO); 5′-ATGCAGAGTCCATGAATATCAACTTT AA-3′.